Elevation of Bcl2 expression in artery spiralis of pregnant Rattus norvegicus infected with Tachyzoite of Toxoplasma gondii with hyperbaric oxygen therapy - Nurdianto, Arif Rahman; Aryati, Aryati; Suryokusumo, Mohammad Guritno; Mufasirin, Mufasirin (Qanun Medika - Medical Journal Faculty of Medicine Muhammadiyah Surabaya, 2019)
ABSTRACT Spiral artery apoptosis plays a role in the process of abortion. Low Bcl2 expression found in abortion and in spiral artery. In pregnancy, Toxoplasmosis infection is found to increase apoptosis in spiral arteries. Hyperbaric Oxygen Therapy (HBOT) improves the expression of Bcl-2. This study aims to determine the effects of Hyperbaric Oxygen therapy in enhancing the expressions of Bcl2 in artery spiralis of pregnant rats infected with tachyzoite of Toxoplasma gondii. This is an experiment with a ‘randomized control group of post-test only design’ on 37 Rattus novergicus Sprague Dawley rats. Rats were divided into four groups. The group A is pregnant rats infected with 103 tachyzoites via intraperitoneal injection and received 10 sessions of HBOT 2.4 ATA in 3x30 minutes. Group B is pregnant only and received HBOT. Group C is pregnant and infected with tachyzoite but did not received HBOT. And the last, Group D is pregnant rats with no infection and did not received HBOT. Examinations of Bcl2 expressions were performed on day-5 after HBOT (twice a day). The Bcl2 expression was measured with immunohistochemistry. All data were tested with One-way ANOVA from SPSS 21. There is an increased expression of Bcl2 spiralis artery in the Group A. There was a significant difference between Group A and Group C with a value of p=0.042. HBOT can increase the expression of Bcl2 from the spiral arteries of rats, in the provision of HBOT 2.4 ATA for 3x30 minutes, 10 times in 5 days. Keywords: Toxoplasma gondii, tachyzoite, Hyperbaric Oxygen Therapy, Bcl2, spiralis artery Correspondence to: didins99@gmail.com ABSTRAK Apoptosis arteri spiralis berperan dalam proses aborsi. Ekspresi Bcl2 rendah ditemukan pada aborsi dan di arteri spiral. Pada kehamilan, infeksi Toxoplasmosis ditemukan meningkatkan apoptosis pada arteri spiralis. Terapi Oksigen Hiperbarik (HBOT) meningkatkan ekspresi Bcl-2. Ini adalah penelitian eksperimental dengan desain post-test only pada 37 hamil Rattus novergicus Sprague Dawley, maka tikus dibagi menjadi 4 kelompok. Grup A HBOT adalah tikus hamil yang terinfeksi tachyzoite yang menerima terapi 10 sesi HBOT 2.4 ATA dalam 3x30 menit; kelompok B adalah Hamil saja dan tidak mendapat HBOT; kelompok C Hamil dan terinfeksi tachyzoite T.gondii tetapi tidak menerima HBOT; dan kelompok D adalah tikus hamil normal. Setiap tikus hamil yang terinfeksi diberi 103 Tachyzoite Toxoplasma gondii melalui intraperitoneal. Pemeriksaan ekspresi Bcl2 dilakukan pada hari ke-5 setelah HBOT (dua kali sehari). Tikus terbunuh dan kadar Bcl2 Arteri spiralis diukur dengan pemeriksaan Immunohistokimia. Semua data dianalisis dengan uji ANOVA dengan Program SPSS 21. Pada studi ini menunjukkan terapi Oksigen Hiperbarik dapat meningkatkan Ekspresi Bcl2 Arteri Spiralis dengan dosis 2.4 ATA selama 3x30 menit dalam 10 sesi selama 5 hari terapi. Studi ini menyimpulkan bahwa HBOT dapat meningkatkan ekspresi Bcl2 dalam arteri spiralis, dalam pemberian HBO 2.4 ATA selama 3x30 menit dalam 10 sesi. Kata kunci: HBOT, Arteri spiralis, Bcl2, Tachyzoite Toxoplasma gondii Korespondensi: didins99@gmail.com